Variation of Chemical Constituents and Relative Nutritive Value with Plant Maturity in Chrysopogon gryllus (Linn.) Trin and Eragrostis nigra Nees of Kumaun Hills - PANT, C.S.; DHAMI, K.S. (Asian Journal of Chemistry, 2010)
Chemical investigation of indigenous fodder grasses, viz., Chrysopogon gryllus (Linn) Trin and Eragrostis nigra Nees of Naintial was carried out at different stages of plant maturity from July to October to assess their relative nutritive value because these grasses are commonly used as green fodder by local people during monsoon season and also stored as hay for feeding the cattle during dry winter and summer seasons. These grasses were found to contain sufficiently high level of chemical ingredients, viz., protein, ether extract (crude fat), sugars, ash and minerals and hence are assessed as good quality fodders.